Constructions and Criteria for the Theory of Abuse in the Right in the Law - Ali Abd Al Reda, Nasif; Musaa Fahimi, Prof.Dr.Aaziz Allah; Sadeghi, Dr. Mohammad (Basra studies journal, 2022)
The idea of arbitrariness in the use of the truth, according to what the jurists of Islamic law see, is based on many verses of the Holy Quran and the blessed hadiths narrated about the Prophet (may Allah’s peace and blessings be upon him), which confirm that the use of the truth is legitimate, if it is done honestly and sincere intention Although the jurists of the public of Sharia have approved this idea of arbitrariness, but it has never been the subject of consensus or agreement, there is a team that opposes the idea and opposes it represented by the virtual doctrine and at the head of these jurists (Ibn Hazm), and it stated in its author (Al-Mahalli) Malik said, "This is forbidden from all this," Abu Muhammad said, "This is a mistake, because everyone has the first right to his right, and the neighbor has no right to benefit from the wall of his neighbor except where the text came, and there is no difference between tearing down his wall, so it is not charged with rebuilding it, and he says to his neighbor to cover yourself if you want, and it is to demolish the wall of himself, and there is no difference between the ceiling and seeing from it and between the bottom of the house and seeing it, and there is no difference between opening a skylight and opening it to air, and both things can be seen from him, and there was no Quran, nor a Sunnah, nor true, or true saying of a friend prevents one from opening in his right. His wall is what he wants If they invoke the news, "There is no harm and no harm," this is not true because it came as a messenger or from a path in which Zuhair bin Thabet is weak, but its meaning is true and not greater than preventing one from acting in one’s own money in consideration of the benefit of others, this is really harm.